Insights into carbon nanotube and graphene formation mechanisms from molecular simulations: a review. (9th March 2015) - Page, A J; Ding, F; Irle, S; Morokuma, K
Abstract: The discovery of carbon nanotubes (CNTs) and graphene over the last two decades has heralded a new era in physics, chemistry and nanotechnology. During this time, intense efforts have been made towards understanding the atomic-scale mechanisms by which these remarkable nanostructures grow. Molecular simulations have made significant contributions in this regard; indeed, they are responsible for many of the key discoveries and advancements towards this goal. Here we review molecular simulations of CNT and graphene growth, and in doing so we highlight the many invaluable insights gained from molecular simulations into these complex nanoscale self-assembly processes. This review highlights an often-overlooked aspect of CNT and graphene formation—that the two processes, although seldom discussed in the same terms, are in fact remarkably similar. Both can be viewed as a 0D → 1D → 2D transformation, which converts carbon atoms (0D) to polyyne chains (1D) to a complete sp 2 -carbon network (2D). The difference in the final structure (CNT or graphene) is determined only by the curvature of the catalyst and the strength of the carbon–metal interaction. We conclude our review by summarizing the present shortcomings of CNT/graphene growth simulations, and future challenges to this important area.